A comparative study on dengue and malaria infections and analysis on the prevalence of co-infection from a rural tertiary care hospital - P. R., Dhanya; K., Shilpa; Hittinahalli, Vivek (International Journal of Research in Medical Sciences, 2018)
Background: To compare dengue fever and malaria infection cases from a rural tertiary care hospital. Methods: Samples from January 2017 to February 2018 which had come to the Department of Microbiology at East Point College of Medical Science and Research Centre were included in the study. Serological diagnosis of dengue was done using the rapid dengue day 1 test which detects NS1, IgM and IgG. This test can be performed using serum, plasma or whole blood. Malarial parasites were identified by peripheral smear for malaria by Leishman’s stain and Jaswant Singh Battacharji (JSB) stain, rapid tests were performed by using advantage mal card, which detects plasmodium falciparum and plasmodium vivax by using human whole blood. Results: Monthly analysis is done for dengue samples and malaria samples were done during January 2017 to February 2018. Positive samples are then analysed according to NS1 positive cases, IgM positive cases, IgG positive cases, NS1 and IgM combined cases, NS1 and IgG combined cases and IgM and IgG combined cases for dengue. In case of malaria vivax and falciparum cases were compared. Samples are then compared among different age groups. Under 15 age- group there were 32 positive cases of NS1, 1 case of IgM and IgG combined positive and 1 case of P. falciparum infection. In 16-50 age-group 244 cases were dengue NS1 positive, 1 case positive for NS1 and IgM combined, 1 case for NS1 and IgG combined, 5 cases for IgM and IgG combined, 11 cases of P. vivax and 3 cases of P. falciparum. Above 50 age-group had 27 NS1 positive cases and 1 case of IgM and IgG combined. NS1 and Plasmodium vivax species positives were more from dengue and malaria infection. Conclusions: From July 2017 to October 2017 dengue and malaria cases were drastically increased. Malariacases drops from November to December 2017 and again raised from January to February 2018, which shows seasonal variations. So, we conclude that viral and parasitic infection mainly occurs in July to September months and has to be ruled by proper clinical diagnosis.